2007
DOI: 10.1211/jpp.59.8.0014
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and analgesic activities of the ethanolic extracts from Zanthoxylum riedelianum (Rutaceae) leaves and stem bark

Abstract: We have evaluated the anti-inflammatory and analgesic properties of the leaves (LCE) and stem bark (BCE) crude extracts of Zanthoxylum riedelianum (Rutaceae). Different fractions of the stem bark extract (hexane, BCEH; dichloromethane, BCED; ethyl acetate, BCEE; and lyophilized aqueous residual, BCEW) were also investigated. We studied the effects of the extracts and fractions using the rat paw oedema test induced by carrageenan, dextran, histamine or nystatin; the mouse abdominal constriction test; the mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 45 publications
6
27
0
4
Order By: Relevance
“…Our results revealed that the sesame oil and sesamin reduced the abdominal writhes induced by acetic acid showing antinociceptive effect. In addition, our data extend previous observations showing that palmitic acetic [7] and sesamin [45,46] inhibit acid-induced in mice. The mechanism of this effect could be related the prostaglandin synthesis inhibition as suggested for linoleic acid, one of the constituents of the sesame oil [3].…”
Section: Discussionsupporting
confidence: 91%
“…Our results revealed that the sesame oil and sesamin reduced the abdominal writhes induced by acetic acid showing antinociceptive effect. In addition, our data extend previous observations showing that palmitic acetic [7] and sesamin [45,46] inhibit acid-induced in mice. The mechanism of this effect could be related the prostaglandin synthesis inhibition as suggested for linoleic acid, one of the constituents of the sesame oil [3].…”
Section: Discussionsupporting
confidence: 91%
“…These results are in accordance with previous findings from the literature in which lupeol and lupeol acetate were reported to exhibit higher anti-inflammatory activity than indomethacin in rat and mouse models of inflammation [27,28]. Lupeol was reported to act as an anti-inflammatory agent with a mechanism similar to COX-selective inhibitor drugs [29], as well as, in-vitro inhibition of PGE2 and tumournecrosis factor-α [30]. Ursolic acid was as well reported to have anti-inflammatory, in addition to antioxidant and cytotoxic activities [31].…”
Section: Table 4 Effects Of O Elliptica Extracts and Indomethacin Osupporting
confidence: 92%
“…Employing inflammation-associated mouse models, several studies have established the anti-inflammatory potential of lupeol (Davis et al, 1994;Akihisa et al, 1996;Geetha and Varalakshmi 1999b;Fernández et al, 2001a,b;Ramirez Apan et al, 2004;Lima et al, 2007). Lupeol treatment has been shown to reduce the inflammation in mouse models of arthritis and bronchial asthma (Geetha and Varalakshmi, 2001;Vasconcelos et al, 2008).…”
Section: Cancermentioning
confidence: 99%